2012
DOI: 10.1021/cg300454q
|View full text |Cite
|
Sign up to set email alerts
|

Photochromism Control of Salicylideneaniline Derivatives by Acid–Base Co-Crystallization

Abstract: Acid–base co-crystallization has been used to control the photochromic reactivities of salicylideneaniline derivatives in co-crystals. The series of co-crystals N-salicylidene-3-carboxyaniline (1) with 2-aminopyridine (a), guanylthiourea (b), cytosine (c), 4,4′-bipyridyl (d), piperazine anhydrous (e), 1,3-di-o-tolylguanidine (f), and dibenzylamine (g) and N-salicylidene-4-carboxyaniline (2) with 4,4′-bipyridine (d) and N,N-dibenzylamine (g) have been synthesized. The weak photochromic compound 1 becomes nonpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 30 publications
3
61
0
Order By: Relevance
“…The preferred geometry about the NC bond can be expected to have the salicylidene−azomethine and p-carboxyphenyl fragments in different planes, taking as reference what has been found for other molecules bearing similar structural elements. 28,29 Considering points (i)−(iv) above, it can be concluded that the number of relevant structures for each enol isomer (E and Z forms, which are defined by the orientation of the groups around the CN bond) is in fact rather small.…”
Section: Resultsmentioning
confidence: 99%
“…The preferred geometry about the NC bond can be expected to have the salicylidene−azomethine and p-carboxyphenyl fragments in different planes, taking as reference what has been found for other molecules bearing similar structural elements. 28,29 Considering points (i)−(iv) above, it can be concluded that the number of relevant structures for each enol isomer (E and Z forms, which are defined by the orientation of the groups around the CN bond) is in fact rather small.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas photochemical back reactions are characterised by bi‐exponential behaviour, the thermal fading processes are well described by first‐order reactions. A two‐stage thermal decay of the trans ‐keto form of anils in the solid state has been previously reported . It can be observed that the two co‐crystals show much faster back reactions than that of simple compound 2 : the photoconversion kinetics of the trans ‐keto tautomer are of the order of tens of seconds for 2 2 ⋅I2F4 and 3 2 ⋅I2F4 and tens of minutes for 2 (Figures S17–S19 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 73%
“…At wo-stage thermal decay of the trans-keto form of anils in the solid state has been previously reported. [9,12,13,62] It can be observed that the two co-crystals show much faster back reactions than that of simple compound 2:t he photoconversion kinetics of the trans-keto tautomer are of the order of tens of seconds for 2 2 ·I2F4 and 3 2 ·I2F4 and tens of minutes for 2 (Figures S17-S19 in the SupportingI nformation). Concerning thermalf ading, conversion times of 604, 65 and 186 min have been measured for the trans-keto form of 2, 2 2 ·I2F4 and 3 2 ·I2F4,r espectively; this confirms that 2 undergoes the slowest process.…”
Section: Thermo-and Photochromic Behaviourmentioning
confidence: 99%
“…To this end, several elegant strategies have been developed to overcome the aws of small molecule probes, for example conjugating or loading them into inorganic nanoparticles, micelles, polymers, and so forth. [38][39][40][41][42][43] Of all of the above, polymer-based uorescent chemosensors have several advantages over the others, such as water solubility, exceptional processability, and signal amplication. Hence, efforts have been dedicated to the fabrication of polymeric chemosensors, which contain salicylaldimine Schiff bases.…”
Section: Introductionmentioning
confidence: 99%